In situ dextran synthesis by Weissella confusa Ck15 and Leuconostoc pseudomesenteroides DSM 20193 and their effect on chickpea sourdough bread. (20th May 2021) - Galli, Viola; Venturi, Manuel; Cardone, Gaetano; Pini, Niccolò; Marti, Alessandra; Granchi, Lisa
Summary: This work evaluated, for the first time, the impact of in situ dextran (with different branching degree) produced by Weissella confusa Ck15 and Leuconostoc pseudomesenteroides DSM 20193 strains on the technological properties of chickpea–wheat sourdough bread prepared with three levels of chickpea flour (20, 30 and 40 g/100 g). In addition Lactiplantibacillus plantarum F8 strain (not dextran producing) and a control without sourdough fermentation were used. Specific volume, crumb hardness and moisture content of breads were evaluated during six days of storage. At the increase of chickpea flour from 20 to 40 g/100 g in the samples, the lowest decrease in bread volume (15%) occurred when W . confusa Ck15 was used. Moreover, these breads showed the lowest crumb hardness at each chickpea flour percentage, 46, 80 and 98 N. Hence, in situ dextran synthesis by W . confusa Ck15 might counteract negative effects caused by gluten‐free chickpea flour on technological properties of bread. Abstract : In situ dextran production by Weissella confusa Ck15 and Leuconostoc pseudomesenteroides DSM 20193 strains positively affected the technological properties of chickpea–wheat sourdough bread.